Monodisperse carboxyl-functionalized poly(ethylene glycol)-coated magnetic poly(glycidyl methacrylate) microspheres: application to the immunocapture of β-amyloid peptides - Horák, Daniel; Hlídková, Helena; Hiraoui, Mohamed; Taverna, Myriam; Proks, Vladimír; Mázl Chánová, Eliška; Smadja, Claire; Kučerová, Zdenka (Macromolecular bioscience, 2014)
Identification and evaluation of small changes in β-amyloid peptide (Aβ) levels in cerebrospinal fluid is of crucial importance for early detection of Alzheimer's disease. Microfluidic detection methods enable effective preconcentration of Aβ using magnetic microparticles coated with Aβ antibodies. Poly(glycidyl methacrylate) microspheres are coated with α-amino-ω-methoxy-PEG5000 /α-amino-ω-Boc-NH-PEG5000 Boc groups deprotected and NH2 succinylated to introduce carboxyl groups. Capillary electrophoresis with laser-induced fluorescence detection confirms the efficient capture of Aβ 1-40 peptides on the microspheres with immobilized monoclonal anti-Aβ 6E10. The capture specificity is confirmed by comparing Aβ 1-40 levels on the anti-IgG-immobilized particles used as a control.
Keywords: Amyloid beta-Peptides; Immunoglobulin G; β-amyloid peptides; skot; Particle Size; Magnetic Phenomena; zvířata; Polyethylene Glycols; Cattle; Peptide Fragments; CE-LIF detection; magnetic; Adsorption; Microspheres; chromatografie afinitní; functionalization; Polymethacrylic Acids; Carboxylic Acids; elektroforéza kapilární; mikroskopie atomárních sil; Chromatography, Affinity; Thermogravimetry; peptidové fragmenty; polyethylenglykoly; imunoglobulin G; magnetické jevy; velikost částic; microspheres; mikrosféry; amyloidní beta-protein; Animals; Electrophoresis, Capillary; termogravimetrie; kyseliny karboxylové; adsorpce; kyseliny polymethakrylové; Microscopy, Atomic Force